Um novo método laboratorial para diagnóstico de parasitos gastrointestinais em cães - Coelho, Willian Marinho Dourado [UNESP]; Gomes, Jancarlo Ferreira; do Amarante, Alessandro Francisco Talamini [UNESP]; Bresciani, Katia Denise Saraiva [UNESP]; Lumina, Giuliano [UNESP]; Koshino-Shimizu, Sumie; Leme, Denise Pereira; Falcão, Alexandre Xavier (FapUNIFESP (SciELO), 2012)
In this study, we aimed to introduce a new technique called TF-Test Modified/Dog for the diagnosis of gastrointestinal parasites in dogs. Fecal samples from 106 dogs were processed by the technique TF-Test Modified/Dog and the techniques of centrifugation-flotation in zinc sulfate, simple-flotation by saturated solution of sodium chloride, direct microscopy exam and TF-Test Conventional. Sensitivity was higher in the TF-Test Modified/Dog (98.41%), followed by flotation in saturated zinc sulfate (77.78%), TF-Test Conventional (73.02%), flotation by saturated sodium chloride (55.55%), and direct microscopy exam (30.16%). The diagnostic efficiency varied from 58.49% to 99.06%, with the highest value also obtained by the new proposed technique. Efficiency level of 99.06% with kappa index 0.979 (almost perfect) was obtained with the TF-Test Modified/Dog. These results represent significant statistical gains (P < 0.05) of 20.63% in sensitivity and 12.27% in efficiency over the best among the other techniques - flotation by saturated zinc sulfate, whose kappa index was 0.738, much lower than that of the TF-Test Modified/Dog. All techniques presented 100% specificity. In this sense, the high sensitivity of the TF-Test Modified/Dog makes it suitable for epidemiological surveys of gastrointestinal parasitosis in dogs, zoonoses control and preventive surveillance programs.
A new laboratorial method for the diagnosis of gastrointestinal parasites in dogs
Keywords: Canine gastrointestinal parasites; Faeces analysis; Parasitological techniques; TF-Test Modified/Dog